El contenido de la justicia en Santo Tomás de Aquino - Larrain, Federico García (Sapientia, 2019)
Aquinas defines justice as “a habit whereby a man renders to each one his due by a constant and perpetual will”. This definition presents the problem of the content of justice. This paper intends to show that the notion of justice in the philosophy of Aquinas is not an empty one and that its content can be found in the wide discussion on this virtue, its parts and its vices. The content of justice is complemented by Aquinas’ ethics, anthropology and metaphysics. Human goods, such as life, freedom, sociability, rationality, even private property, are part of what is due to each one. Aquinas does not discuss at length the question of establishing justice, he leaves it to a case by case examination, because of the primacy of the individual (who is constituent of society and the moral agent) and because of the diversity of contingent reality.